How IPDC Finance Ltd. is re-engineering its business operation process to serve with efficiency - Islam, Gazi Md Tasinul (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.